Microwave-assisted synthesis of few-layered TaTe2 and its application as supercapacitor - Chakravarty, Disha; Kumar, Praveen; Ugale, Vaishali S.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report a simple and rapid microwave-assisted synthesis of tantalum telluride (TaTe2) nanosheets. The ratio of tantalum pentachloride (TaCl5) and elemental tellurium (Te) powder were adjusted in the presence of NaBH4 in such a way as to obtain the TaTe2 nanosheet. The samples were characterized by various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), UV/Vis spectroscopy, photoluminescence (PL) spectroscopy, and XRD. Our SEM, TEM, and AFM results show the formation of sheet-like morphology, while the XRD data confirms the high crystalline quality and stable phase of the TaTe2 formed. The supercapacitor cells were fabricated by using TaTe2 nanosheets as anode material, platinum metal wire as a counterelectrode, and Ag/AgCl as reference electrode. The calculated coulombic efficiency is more than 95%, while the cycle-to-cycle decrease in capacity is less than 5%. The maximum discharge or charging capacity is below 2.4 Wh/kg, which is an ideal characteristic for achieving supercapacitor behavior.
Keywords: Microwave chemistry; Nanostructures; Supercapacitors; Tantalum; Tellurium